DEVELOP OF KNOWLEDGE-BASED SYSTEM (KBS) TO MANAGE CORROSION UNDER INSULATION (CUI) - CHAN, GEORGE WEI XIANG (IRC, 2018)
Corrosion Under Insulation (CUI) normally occurred at petrochemical plant which has been in operation for over 40 years. CUI can be defined as the corrosion occurs on the external surface of the piping when water or vapor is being absorbed or collected in the insulation. Over the years, engineers identified CUI as a critical case but is not being captured and recorded properly. Therefore, inspection of pipes needed to be conducted periodically which involved a lot of cost expenditures. In addition, it is also a challenge to identify the specific area and location to perform the pipe inspection as the piping are all insulated. Other challenges include the significant amount of time and cost to perform the insulation stripping work. An effective and successful managerial method for this issue have so far not been established yet. The purpose of this project is to develop a knowledge-based system to determine the failure of CUI and also the potential locations in order to have a more focused inspection program. This will save a significant amount of cost spent on inspection activity and will generate considerable interest in the industry. Effective implementation of the knowledge-based system for CUI will be able to extend the operating life of the piping, enhancing the asset integrity and improving HSE in a plant.